Recreating the Follicular Environment: A Customized Approach for In Vitro Culture of Bovine Oocytes Based on the Origin and Differentiation State - Luciano, Alberto Maria; Barros, Rodrigo Garcia; Soares, Ana Caroline Silva [UNESP]; Buratini, Jose [UNESP]; Lodde, Valentina; Franciosi, Federica (Springer Nature, 2021)
The mammalian ovary is a large source of oocytes organized into follicles at various stages of folliculogenesis. However, only a limited number of them can be used for in vitro embryo production (IVEP), while most have yet to complete growth and development to attain full meiotic and embryonic developmental competence. While the in vitro growth of primordial follicles in the ovarian cortex has the potential to produce mature oocytes, it is still at an experimental stage. The population of early antral follicles (EAFs), instead, may represent a reserve of oocytes close to completing the growth phase, which might be more easily exploited in vitro and could increase the number of female gametes dedicated to IVEP. Here we present in vitro culture strategies that have been developed utilizing physiological parameters to support the specific needs of oocytes at distinct stages of differentiation, in order to expand the source of female gametes for IVEP by maximizing the attainment of fertilizable oocytes. Furthermore, these culture systems provide powerful tools to dissect the molecular processes that direct the final differentiation of the mammalian oocyte.
Keywords: Chromatin; Cumulus cells; Gap junction; Germinal vesicle; In vitro oocyte growth; Intercellular communication; Meiotic arrest; Oocyte; Oogenesis; Prematuration